서울시 남산 신갈나무림의 식물 군집 및 개체군 동태(2017년∼2023년) - 하민선; Min-seon Ha; 이정은; Jeong-eun Lee; 최훈기; Hun-gi Choi; 한상학; Sang-hak Han; 박정수; Jeong-su Park; 이재연; Jae-yeon Lee; et al. (한국산림과학회지, 2025)
우리나라에서 가장 인구밀도가 높아 인위 및 자연 교란이 지속되는 서울시 남산은 비교적 자연성이 높은 신갈나무림이 넓은 면적을 차지하고 있다는 점에서 생태 가치, 보전 가치 등이 크다. 본 연구는 도시림의 생태적 관리와 유지 방안의 생태학적 근거 자료를 확보하고 이를 활용하고자 서울시 남산의 신갈나무림을 대상으로 6년간(2017년∼2023년) 식물 군집 및 개체군의 동태를 구명하고자 하였다. 따라서 국가장기생태연구를 통해 구축된 서울시 남산 신갈나무림 1 ha (100 m×100 m)를 대상으로 밀도, 고사율과 이입률, 흉고단면적, 흉고직경급 분포, 중요치, 수간건강상태 및 임목 쇠퇴율 분석을 실시하였다. 측정 기간동안, 5개체의 진계목과 23개체의 고사목이 발생한 신갈나무의 연고사율과 연이입율은 각각 0.5% 및 2.2%로 계산되었으며, 2019년 발생한 개체 밀도 감소에 따라 흉고단면적은 감소 후 다시 증가하였다. 우점종으로서 중요치가 가장 높은 신갈나무는 20-30cm의 직경급에서 개체목 밀도가 가장 높은 정규분포를 나타냈고, 꾸준하게 임목쇠퇴율이 증가하고 있었다. 하지만, 작은 직경급에서 개체목 밀도가 높았고, Alive Standing (AS) 유형이 대다수를 차지하여 조사 장소의 우점종이 다른 수종으로 대체될 가능성은 낮은 것으로 판단되었다. 결론적으로, 지속적인 교란에도 불구하고 남산 신갈나무림의 주요 목본 개체군들은 높은 지속가능성을 나타내는 것으로 평가되었다. 앞으로도 도시림 내의 신갈나무림이 잘 유지될 수 있도록 지속적인 모니터링이 요구되는 바이다. Namsan, Seoul, is located at the most densely populated area in Korea and is subject to ongoing anthropogenic and natural disturbances. The large Quercus mongolica forest in Namsan holds significant ecological and conservation value. This study monitored a 1-ha (100 m × 100 m) plot within this forest from 2017-2023 as part of the Korea Long-Term Ecological Research, which aims to provide baseline data for the ecological management and maintenance of urban forests. We analyzed tree density, mortality rate, recruitment rate, breast height area (BHA), diameter distribution, importance values, trunk health status, and tree decline rate. Over the study period, 23 trees died and 5 young individuals were recruited, yielding annual mortality and recruitment rates of 2.2% and 0.5%, respectively. BHA decreased in 2019 due to decrease in density but subsequently recovered. The dominant species, Q. mongolica, was normally distributed, with the highest tree density in the 20-30 cm diameter class. Although the tree decline rate was steadily increasing, the high density of the small diameter class of trees and the prevalence of "alive and standing" trees indicate that Q. mongolica is likely to remain dominant. In conclusion, despite ongoing disturbances, the Q. mongolica forest in Namsan demonstrates a high potential for sustainability. However, continuous monitoring is essential to ensure the long-term maintenance of Q. mongolica forests in urban areas.